ZnO Nanosheets Abundant in Oxygen Vacancies Derived from Metal‐Organic Frameworks for ppb‐Level Gas Sensing. Issue 11 (13th January 2019) - Yuan, Hongye; Aljneibi, Saif Abdulla Ali Alateeqi; Yuan, Jiaren; Wang, Yuxiang; Liu, Hui; Fang, Jie; Tang, Chunhua; Yan, Xiaohong; Cai, Hong; Gu, Yuandong; Pennycook, Stephen John; Tao, Jifang; et al.
Abstract: Surmounting the inhomogeniety issue of gas sensors and realizing their reproducible ppb‐level gas sensing are highly desirable for widespread deployments of sensors to build networks in applications of industrial safety and indoor/outdoor air quality monitoring. Herein, a strategy is proposed to substantially improve the surface homogeneity of sensing materials and gas sensing performance via chip‐level pyrolysis of as‐grown ZIF‐L (ZIF stands for zeolitic imidazolate framework) films to porous and hierarchical zinc oxide (ZnO) nanosheets. A novel approach to generate adjustable oxygen vacancies is demonstrated, through which the electronic structure of sensing materials can be fine‐tuned. Their presence is thoroughly verified by various techniques. The sensing results demonstrate that the resultant oxygen vacancy‐abundant ZnO nanosheets exhibit significantly enhanced sensitivity and shortened response time toward ppb‐level carbon monoxide (CO) and volatile organic compounds encompassing 1, 3‐butadiene, toluene, and tetrachloroethylene, which can be ascribed to several reasons including unpaired electrons, consequent bandgap narrowing, increased specific surface area, and hierarchical micro–mesoporous structures. This facile approach sheds light on the rational design of sensing materials via defect engineering, and can facilitate the mass production, commercialization, and large‐scale deployments of sensors with controllable morphology and superior sensing performance targeted for ultratrace gas detection. Abstract : A facile approach for designing sensing materials via rational defect engineering to tune the electronic structure of on‐chip MOF‐derived hierarchical ZnOs and thus sensing properties is proposed. The resultant homogeneous ZnO layer with abundant oxygen vacancies exhibits significantly enhanced sensitivity and short response time toward ppb‐level carbon monoxide and volatile organic compounds.